2014
DOI: 10.1371/journal.pone.0101651
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Color-Odor Associations

Abstract: Colors and odors are associated; for instance, people typically match the smell of strawberries to the color pink or red. These associations are forms of crossmodal correspondences. Recently, there has been discussion about the extent to which these correspondences arise for structural reasons (i.e., an inherent mapping between color and odor), statistical reasons (i.e., covariance in experience), and/or semantically-mediated reasons (i.e., stemming from language). The present study probed this question by tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 35 publications
2
51
1
Order By: Relevance
“…These intriguing correspondences appear to be both robust across individuals (within a culture, see Levitan et al 2014) and stable over time (Gilbert et al 1996). The results of the present study confirm the existence of a number of odourcolour associations that are common to participants from France and Britain (which is critical given the replication crisis that some fields are currently facing, e.g.…”
Section: Resultssupporting
confidence: 78%
“…These intriguing correspondences appear to be both robust across individuals (within a culture, see Levitan et al 2014) and stable over time (Gilbert et al 1996). The results of the present study confirm the existence of a number of odourcolour associations that are common to participants from France and Britain (which is critical given the replication crisis that some fields are currently facing, e.g.…”
Section: Resultssupporting
confidence: 78%
“…Results obtained in this study are closed to the ones reported in literature, where panelists have smelt odorants[30][31][32][33][34][35][36] (Supplementary…”
supporting
confidence: 45%
“…29,30 In most of the studies on odor/color correlation, panelists are first asked to smell prior to attribute a color. A cross-modal relationship between both parameters has already been demonstrated.…”
Section: And the Total Olfactorymentioning
confidence: 99%
“…I do not intend to spend much space to argue against this erroneous assumption, as numerous theories and abundant studies have shown that human behavior unfolds as a dynamic transaction between an active individual and his changing environment (e.g., Coll & Marks, 2009; Hermans, 2001; Hong et al, 2000; Kitayama & Cohen D., 2007; Shweder et al, 1998; Sternberg, 2014). Many “basic” psychological processes and constructs for which culture is typically assumed to be irrelevant, such as neuronal functioning (Chiao et al, 2013; Park & Huang, 2010), sensation (Levitan, Ren, Woods, Boesveldt, Chan, McKenzie et al, 2014; Yeshurun & Sobel, 2010), visual illusions (Kitayama, Duffy, Kawamura, & Larsen, 2003; McCauley & Henrich, 2006), face processing (Kelly, Liu, Rodger, Miellet, Ge, & Caldara, 2011), and color perception (Roberson, Davidoff, Davies, & Shapiro, 2005; Taylor, Clifford, & Franklin, 2013), have been shown to be sensitive to cultural influences. Even simple taste preferences are subject to local community practices rather than being part of human genetic composition as commonly assumed.…”
Section: Assumption 4: Cultural Psychology Is Irrelevant To Basic Psymentioning
confidence: 99%